Humans are Social and Emotional Beings - Jessica Trach; Keerthi Ramanujan; Clifford Saron; Nandini Chatterjee Singh (Unesco, 2022)
Humans as a species evolved to be social. We have an innate, biologically-driven ability to develop and form interpersonal connections. These social bonds, formed early in life, also create the foundation for human beings to coexist in and across groups, and are a vital and essential part of the human experience. Understanding the role that relationships play in our personal well-being is necessary for informing broader social and educational policies aimed at improving the well-being of future generations, and indeed, society as a whole. Interventions aimed at fostering and promoting peaceful communities within rapidly changing socio-ecological climates must first embrace the fact that human beings are social beings. Moreover, our social interactions are often the basis for experiencing intense emotions, positive or negative. In this chapter, we discuss the idea that humans are complex social and emotional beings whose well-being depends on learning to communicate their needs to each other effectively and manage their emotions in healthy ways.
Rethinking Learning: A Review of Social and Emotional Learning for Education Systems